The Effect of Interest Rate Spread on the Profitability of Nepalese Commercial Bank - Acharya, Kabi Raj; Vyas, Surendra Kumar (Patan Prospective Journal, 2022)
This study examines the impact of the interest rate spread on the profitability of Nepalese commercial banks by using the data from mid-July 2011/12 to 2020/21.This study employs a quantitative approach to examine the effect on twenty-six commercial banks. The results show that interest rate spread positively affects firm performance. One percentage increase in interest rate spread increases return on assets by 0.137%, return on equity by 1.37%, and earnings per share by 8.11%.